Clinical course of severe patients with COVID-19 treated with tocilizumab: report from a cohort study in Spain. Issue 2 (1st February 2021) - Chamorro-de-Vega, Esther; Rodriguez-Gonzalez, Carmen-Guadalupe; Manrique-Rodríguez, Silvia; Lobato-Matilla, Elena; García-Moreno, Felix; Olmedo, Maria; Correa-Rocha, Rafael; Valerio, Maricela; Aldámiz-Echevarria, Teresa; Machado, Marina; Sancho-Gonzalez, Milagros; Lopez-Bernaldo-de-Quirós, Juan Carlos; et al.
ABSTRACT: Background : We report the long-term outcomes, changes in laboratory parameters, the incidence of secondary nosocomial infections and treatment cost of a Spanish cohort of patients with severe COVID-19 that received tocilizumab (TCZ). Methods : Retrospective cohort of PCR confirmed adult patients who received TCZ from March 1 to 24, 2020 in a tertiary hospital was analyzed. Patients were followed up until 10 May 2020. Results : We included 162 patients (median age 64 years; 70.4% male). At time of TCZ administration, 48.1% of patients were on invasive mechanical ventilation (IMV). Over a median follow-up of 53 days, 46.9% of patients were discharge in good conditions and 19.8% were still hospitalized. The overall mortality was 33.3%, being higher in patients on IMV than those who did not (46.2% vs 26.7%, P < 0.001). A significant improvement in the lymphocyte count, C-reactive protein, lactate dehydrogenase, and D-dimer was observed. Overall, 43.2% patients presented nosocomial infections, causing death in 8%. Infections were more prevalent in ICU units (63.0% vs 17.1%, P < 0.001). The total cost of TCZ was €371, 784. Conclusions : Among the patients who used TCZ, one third died, regardless the improvement in some inflammatory biomarkers. The incidence of secondary nosocomial infections was high.